INTENSI BERWIRAUSAHA DITINJAU DARI ADVERSITY QUOTIENT PADA MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS KATOLIK SOEGIJAPRANATA SEMARANG - Ika Julita; Sumbodo Prabowo, M.Si (Universitas Katolik Soegijapranata, 2018)
This study aims to determine the relationship between adversity quotient with the intention of entrepreneurship in the students of Management Studies Program Catholic University Soegijapranata Semarang. Hypothesis of this research is there is positive relation between adversity quotient with entrepreneurship intention to student of Management Study Program of Catholic University Soegijapranata Semarang. The population of this research are students of Management Studies Program of Catholic University of Soegijapranata Semarang force 2013 and 2014 which take the entrepreneurship concentration. The sampling technique used purposive sampling and accidental technique. Subjects who got as many as 38 students, with students of force 2013 say 16 people and force 2014 with 22 people. The data analysis is a measure of scale, with Pearson's exclusive Product Moment technique. The result of data analysis shows that adversity quotient is highly positive correlation to entrepreneurship intention, which reported with rxy value = 0,561 with p value